El Clima Organizacional en la Dirección Distrital 11D01-Loja del Ministerio de Inclusión Económica y Social “MIES”, año 2018 - Santander Ludeña, Karen Esthefania (2019)
The main objective of this research work is to diagnose the Organizational Climate in the District Directorate 11D01- Loja of the Ministry of Economic and Social Inclusion “MIES”, year 2018, in order to understand the current reality of this institution. To determine the diagnosis, we worked with a target population made up of 43 officials, the same ones who were surveyed and at the same time 2 of them were interviewed, to determine their perspective on the work environment within the institution. In the same way, the methods applied to the study were the scientific, descriptive and analytical-synthetic that were used to determine the results of the surveys and interviews, the Likert scale methodology that measures the perception and expectations of the officials was applied. Once applied the investigation techniques it was obtained as a result, that the factors that condition the work; environmental conditions, ergonomic conditions and economic conditions are all in a category that are almost never satisfied with these factors that often occur within the institution. It was also found that the variables of the organizational climate are in a hierarchy of dissatisfaction, these being: leadership, motivation, communication and structure, problems that are reflected in the work environment in a negative way. Thus, concluding that the officials are not in harmony and total satisfaction in the District Department 11D01- Loja “MIES”.